Nutrient composition, antioxidant and hypoglycemic effect of bitter gourd (Momordica charantia L.) - Krishnendu J R (Department of home science, College of agriculture, 2015)
The present investigation entitled, “Nutrient composition, antioxidant and hypoglycemic effect of bitter gourd (Momordica charantia L.)” was conducted in Thiruvanathapuram district during the period of 2012- 2015 with an objective to study the nutrient composition, phytochemical analysis, antioxidant activities of the selected bitter gourd types along with assessing its hypoglycemic effect on type 2 diabetes mellitus patients. Four types of commercially cultivated bitter gourd viz., light green small, light green big, dark green small, dark green big along with nei paval were selected for the study. The chemical/ nutrient composition, phytochemical and antioxidant activities of the selected types were carried out both in fresh and processed (powdered) forms and the best type was selected (large green) to ascertain the clinical efficacy of the bitter gourd powder. Investigations such as shelf life quality, yield ratio, cost of production, glycemic index and glycemic load were also determined. Significant differences were found in the nutrient content of fresh and dried bitter gourd types. The highest protein, moisture, vitamin C and folic acid were found in light green big both in the case of fresh and dried samples. The total essential and non essential amino acids were also found highest in light green big. Highest carbohydrate content was observed in light green small type both in the case of fresh and dried samples. β carotene content was found to be highest in neipaval both in fresh and dry samples (140.03 mcg/ 100g and 98.93 mcg/ 100g respectively). In the case of mineral analysis, highest calcium, phosphorus, sodium, manganese, copper and zinc content were observed in light green big. The potassium and iron content was found to be highest in nei paval both fresh and dried samples. Quantitative estimation of phytochemicals revealed that, highest polyphenol content was noticed in light green big type both in the fresh and dried forms (18.76 mg and 74.67 mg respectively). The highest flavonoid content was found in light green big. The alkaloid content of bitter gourd samples (fresh) ranged between 0.10 to 0.27 per cent where as in the case of dried bitter gourd samples it ranged between 0.90 to 1.01 per cent. Tannin content was found higher in nei paval. Saponin and charantin content was found highest in light green big while lectin content was observed to be higher in dark green small type. Antioxidant activity in the present study revealed that fresh light green big type had the highest DPPH activity with an IC50 value of 50.88 µg/ ml in methanol solvent. The hydroxyl radical scavenging activity of light green big was found to be higher both in the case of fresh and dried bitter gourd samples with IC50 value of 50.95 µg/ ml and 50.10 µg/ ml respectively. Fresh light green small types showed higher superoxide anion radical scavenging activity with an IC50 value of 50.36 µg/ ml but in dried samples, the value was 49.76 µg/ ml. Antioxidant activity ranged with an IC50 value of 50.09 µg/ ml to 61.90 µg/ ml in fresh bitter gourd samples. Maximum antioxidant capacity was observed in light green big fresh (50.09 µg/ ml) and in the case of dried bitter gourd samples, the highest antioxidant activity was observed in light green big (50.07 µg/ ml). Assessment of the shelf life qualities of the bitter gourd powder revealed that mean moisture level of bitter gourd powder after six month storage was 6.63 per cent. The peroxide content was noticed in the powder only in 5th month (0.10 meq/100 g) and 6th month (0.12 meq/100 g) of storage. During the storage period of six months, bacterial colonies were observed in the 5th month (1×107cuf/g) and 6th month (2×107 cuf/g) and were only in negligible amounts.